Legal Updates on Copyright Royalty Governance in Indonesia - Hendro Tri Subiyantoro; Evita Isretno Israhadi (CV. Green Publisher Indonesia, 2026)
This research aims to analyze the legal regulations and implementation problems of copyright royalty governance in Indonesia and to formulate legal reforms to achieve certainty and justice for creators. This study employs both a statutory approach and a conceptual approach within a normative juridical research methodology. Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021 concerning the Management of Song and/or Music Copyright Royalties serve as the primary legal materials used in this study, while secondary legal materials include scholarly literature, academic journals, and expert doctrines. The research findings indicate that, normatively, Indonesia's copyright royalty regulation system has provided a solid legal foundation for creators' economic rights through a royalty management mechanism administered by the Lembaga Manajemen Kolektif Nasional (LMKN) and the Lembaga Manajemen Kolektif (LMK). However, a number of issues persist in practice, including the potential for overlapping jurisdiction among royalty management organizations, low levels of compliance among music users in paying royalties, and insufficient transparency in the collection and distribution of royalties. These circumstances reveal a discrepancy between the relevant legal standards and their application in practice. Legal reform is therefore needed through strengthened regulations, increased transparency in royalty management, the development of an integrated information technology system, and the reinforcement of oversight and law enforcement mechanisms. These reforms are expected to produce a more effective royalty governance system, provide legal certainty, and improve the welfare of creators, thereby supporting the development of the creative industry in Indonesia.